2021
DOI: 10.31486/toj.20.0067
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Papillary Thyroid Cancer to the Liver: The Central Role of a Multidisciplinary Approach to Treatment

Abstract: Background: Differentiated thyroid cancer (DTC) is comprised of papillary and follicular subtypes, and both have an overall excellent long-term prognosis. Patients with localized DTC that is successfully treated, usually with surgery, exhibit long-term survival well above 90%. In contrast, patients who develop distant metastatic disease have a significantly worse overall prognosis and outcome, often with disease that is refractory to conventional therapy such as surgery, radioactive iodine, and horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The serum levels of CA19-9 in previously reported patients with liver metastasis of PTC were normal in one patient and not described in 4 patients [3][4][5][6][7]. Since serum levels of CA19-9 are not usually measured in patients with PTC, the percentage of elevated serum CA19-9 levels in patients with PTC is not known.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The serum levels of CA19-9 in previously reported patients with liver metastasis of PTC were normal in one patient and not described in 4 patients [3][4][5][6][7]. Since serum levels of CA19-9 are not usually measured in patients with PTC, the percentage of elevated serum CA19-9 levels in patients with PTC is not known.…”
Section: Discussionmentioning
confidence: 79%
“…The major sites of distant metastases from PTC are the lung and bone. However, to date, there have been few reports of liver metastases in patients with PTC [1][2][3][4][5][6][7]. As liver metastases are usually found along with other distant metastases sites and are nearly always multiple or diffuse [7], it is even more unusual to encounter isolated resectable liver metastases from PTC.…”
Section: Discussionmentioning
confidence: 99%
“…The first treatment for the recurrence and distant metastasis of DTC is generally RAI therapy. Riker reported that lenvatinib was used as initial treatment for a patient with advanced liver metastasis of thyroid papillary cancer liver metastasis before thyroidectomy and RAI [ 7 ]. Depending on the condition of distant metastatic organs, TKI treatment before RAI may be effect to obtain good disease control.…”
Section: Discussionmentioning
confidence: 99%
“…The patient then developed multiple bone metastasis at 33 months and died. The full clinical course and treatment was approximately 39 months [13]. All 3 MTC patients remained recurrence-free at follow-up.…”
Section: Postoperative Treatment and Follow-upmentioning
confidence: 99%